Infliximab in spondyloarthropathy associated with Crohn's disease: an open study on the efficacy of inducing and maintaining remission of musculoskeletal and gut manifestations. Issue 12 (5th August 2004) - Generini, S; Giacomelli, R; Fedi, R; Fulminis, A; Pignone, A; Frieri, G; Del Rosso, A; Viscido, A; Galletti, B; Fazzi, M; Tonelli, F; Matucci-Cerinic, M
Abstract : Objective: To evaluate the efficacy and tolerability of anti-tumour necrosis factor α (TNFα) monoclonal antibody (infliximab) in the treatment of spondyloarthropathy (SpA) associated with active and inactive Crohn's disease (CD). Methods: Twenty four patients with SpA associated with active or inactive CD (16 active, 8 quiescent) were treated with anti-TNFα monoclonal antibody (infliximab) with repeated infusions for a period of 12–18 months. The treatment aimed at ameliorating the general musculoskeletal and spinal pain, controlling peripheral arthritis and enthesitis, decreasing the BASDAI score, modifying acute phase reactants, and reducing CD activity. Results: Infliximab improved both gastrointestinal (p<0.01) and overall articular symptoms (BASDAI, p<0.01; general musculoskeletal and spinal pain, p<0.01; peripheral arthritis, p<0.01) in patients with active CD. Additionally, infliximab effectively controlled not only axial involvement and peripheral arthritis but also enthesitis (p<0.01) and prevented inflammatory bowel disease reactivation in patients with inactive CD and low inflammatory markers. Amelioration of gut and musculoskeletal involvement persisted for up to 12 months. Conclusion: Infliximab may act on the inflammation of entheses and of periarticular structures, which usually does not cause a change in the haematological markers that are the main indicators of pain and joint ankylosis in SpA. Infliximab induces and maintains remission of CD while at the same time treating active and severe SpA, suggesting that it should be the preferred drug for the treatment of active and severe SpA associated with active or quiescent CD.